Centralised laboratory - UMP, PNC (Penerbit UMP, 2012)
The idea for Universiti Malaysia Pahang's Central Laboratory Services was sparked when a need arose to establish an ISO/IEC 17025 accredited analytical laboratory for research, commercialization and enterprises.